Pathogenesis of Keratoconus: the role of inflammation - Marta Fagulha Castanheira (2020)
Purpose: Keratoconus is an ectatic disease characterized by corneal stroma thinning and protrusion, which results in visual impairment. Originally it was believed that keratoconus did not have an inflammatory component given the absence of inflammatory clinical signs. However, it has been shown that there is an underlying inflammatory mechanism in keratoconus pathogenesis. Since these mechanisms are not entirely understood, there is an increasingly amount of studies that focus on comprehending this subject. The aim of this article is to systematically review articles published in the last 5 years about the role of inflammation in the pathogenesis of keratoconus, discuss its results and contribution to profound the knowledge of the disease's mechanism. Materials and Methods: We searched in Pubmed database, for articles published in the last 5 years related to the role of inflammation in keratoconus pathogenesis. Results: We found 112 articles but repeated articles, review papers or articles that did not mention aspects related to inflammation in keratoconus were excluded, resulting in a total of 26 papers. Conclusion: Additional evidence of increased oxidative status and the role of inflammation have been shown by various studies. These studies contributed to the advance knowledge of keratoconus pathogenesis and may be essential for designing new studies that may culminate on the formulation of new biomarkers to an earlier diagnosis and development of more effective and safe therapeutics. Further randomized prospective studies with larger samples are essential to obtain stronger evidence and evaluate the relationship between these investigated molecules and keratoconus development and severity.